2023
DOI: 10.1186/s12890-023-02480-x
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk and exposure to air pollution: a multicenter North China case–control study involving 14604 subjects

Abstract: Background For North Chinese lung cancer patients, there is limited study on the distribution of air pollution and smoking related features based on analyses of large-scale, high-quality population datasets. The aim of the study was to fully analyze risk factors for 14604 Subjects. Methods Participants and controls were recruited in 11 cities of North China. Participants’ basic information (sex, age, marital status, occupation, height, and weight),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In the past decades, the patterns of cancer epidemiology has changed dramatically caused by multiple factors, such as environmental pollution, and unhealthy lifestyles [ 14 ]. A number of clinical studies suggested a strong correlation between exposure to environmental pollution and the incidence and mortality rates of cancer [ [16] , [17] , [18] ], which was consistent with results in animal models [ 19 , 20 ]. In addition, a series of studies have revealed that the disruption of the endocrine system plays significant roles in the development of breast cancer [ 21 ], prostate cancer [ 22 ], thyroid cancer [ 23 ], and endometrial cancer [ 24 ].…”
Section: Introductionsupporting
confidence: 72%
“…In the past decades, the patterns of cancer epidemiology has changed dramatically caused by multiple factors, such as environmental pollution, and unhealthy lifestyles [ 14 ]. A number of clinical studies suggested a strong correlation between exposure to environmental pollution and the incidence and mortality rates of cancer [ [16] , [17] , [18] ], which was consistent with results in animal models [ 19 , 20 ]. In addition, a series of studies have revealed that the disruption of the endocrine system plays significant roles in the development of breast cancer [ 21 ], prostate cancer [ 22 ], thyroid cancer [ 23 ], and endometrial cancer [ 24 ].…”
Section: Introductionsupporting
confidence: 72%